Preparation of 4-vinylpyridine (4VP) resin and its adsorption performance for heavy metal ions. Issue 8 (16th January 2017) - Chen, Youning; Zhao, Wei; Zhang, Juncai
Abstract : The study focused on the preparation of a chelating resin with pyridine ring as the functional group. Abstract : The study focused on the preparation of a chelating resin with pyridine ring as the functional group. The 4VP monomer was directly grafted on the surface of CMPS resin via SI-ATRP, and the performance of adsorption of resin for Cr(vi ), Pb(ii ), Cr(iii ), Zn(ii ), and Cd(ii ) was determined. With the extension of ATRP time and increase of 4VP consumption, the 4VP grafting rate was linearly increased, indicating an increase in the density of the pyridine ring on the resin surface. Adsorption experiments indicated that the adsorption capacity of the resin for the metal ions considerably improved when compared with that of those reported in literature, whereas the desorption rate and reusability were equivalent to those of the conventional resins. When the pH value was greater than 5.0, Pb(ii ), Cr(iii ), Zn(ii ), and Cd(ii ) ions could be adsorbed; however, when the pH value was less than 3.0, Cr(vi ) could be selectively adsorbed. These results are indicative of a potential application of the resin in the treatment of heavy metal wastewater. Therefore, adoption of one-step SI-ATRP is one of the effective methods for preparing a chelating resin with high capacity via the selection of an appropriate functional monomer.